THE INFLUENCE OF BRAND ASSOCIATION AND BRAND PERCEIVED QUALITY ON CONSUMER LOYALTY AT â€œCHATIMEâ€ TEA BEVERAGES IN PALEMBANG - Andrian Angga Kusuma; Zakaria Wahab; Achmad Widad (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2015)
This research aims to determine the influence of Brand Association and Perceived Quality on Consumer Loyalty, as well as to determine which variable is the most dominant to influence Consumer Loyalty at Chatime in Palembang. The population of this research are all consumers of Chatime in Palembang. The samples are consumers who have consumed Chatime for at least 5 times in the last 6 months. This research is a causal research, that use primary data from questionnaire and being analyzed by using descriptive statistics. From the results of the F-test indicates that Brand Association and Brand Perceived Quality simultaneously have positive influence on Consumer Loyalty at 110.626 with a significance level of 0.000. While the results of t-test indicates that the Brand Association and Brand Perceived Quality have positive influence on Consumer Loyalty partially, where Brand Association is the most dominant to influence Consumer Loyalty at Chatime in Palembang with coefficient of 0.504. Then, the R2-test indicates that Brand Association and Brand Perceived Quality have contributions to influence Consumer Loyalty at Chatime in Palembang with percentage 69.5%, while 30.5% are influenced by other factors, such as Brand Awareness, Brand Loyalty, Brand Image, Promotion, Service Quality, Brand Attitude, Brand Profitability, Brand Trust, Customer Satisfaction, etc.Keywords : Brand Association, Brand Perceived Quality, Consumer Loyalty, Chatime, Tea Beverages